Mediating Grief: Postmortem Ritualization After Child Death. - Cacciatore, Joanne; Flint, Melissa (Journal of Loss & Trauma)
The purpose of this study is to better understand the benefits of ritualization for bereaved parents and the factors that influence ritualization. Through phenomenological analyses of 19 in-depth interviews with bereaved parents, the results of this study reveal that bereaved parents engage in ritual to (a) maintain continuing bonds with their child, (b) help them cope by offering them a sense of control, and (c) provide a means toward posttraumatic growth by honoring and memorializing their child. These factors, in turn, appear to mediate grief through meaning reconstruction in the aftermath of the child's life and death within the context of social and cultural influences. Implications for providers are discussed.